Rejecting the Gender Binaries in Hunger Games Trilogy - Ujina Rana (Westcliff University, 2017)
Suzanne Collins, in Hunger Games trilogy, challenges the traditional gender roles by creating mavericks-characters that do not fit into just one gender box but possess both masculine and feminine characteristics. Dystopian novels are all cautionary in nature; alarming us about the gloomy tomorrow if we do not correct our behavior at present. Even though Collins has set her stage in a dystopian world, her gender politics find resonance in the contemporary world.